Pemanfaatan Simulasi PhET dalam Pembelajaran Matematika untuk Meningkatkan Pemahaman Draf Aljabar - Hamid, Abdurahman (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Mathematics learning often face challenges in helping student understand concepts abstract , especially in algebraic material that demands ability think symbolic and representational mathematically . This condition demonstrates the necessity for innovative approaches that enhance learning and facilitate a more concrete and interactive comprehension of concepts. This study aims to analyze the impact of interactive simulations on algebra students' understanding in mathematics learning. The research uses a descriptive approach quantitative with design experiment pseudo through pretest–posttest pattern of the control group . The research population comprised all eighth-grade students at a junior high school, employing cluster sampling to select two classes as the experimental and control groups, resulting in a total of ninety-two respondents. Data collection was conducted through a mathematically validated and reliable understanding draft test. Data analysis was conducted utilizing descriptive and inferential statistics, including normality tests, homogeneity tests, and independent sample t-tests, facilitated by statistical software. The analysis results indicate that mathematics instruction employing interactive simulations significantly enhances algebra students' understanding compared to conventional learning methods. These findings suggest that incorporating simulation media in mathematics education facilitates a more exploratory and student-centered learning experience. The findings of this study offer recommendations for educators to employ interactive technology as a strategy to enhance the quality of mathematics education, while simultaneously contributing theoretically to the reinforcement of constructivist learning models in mathematics education